Study on correspondence between evaluation of vibration sensation, average method, and measurement density of acceleration levels for impact vibration in prefabricated housing floor. (March 2017) - Matsuda, T.; Shimizu, T.
Abstract: This paper reports on an experimental study of a method used to select impact and measurement points to calculate evaluation values based on the distribution properties of a floor to determine the resistance performance in the case of floor vibration (floor impact vibration resistance performance). An evaluation value calculation method for evaluating the resistance performance of an entire floor, rather than that of only representative points under vibration, is studied. A vibration sensation evaluation experiment is also performed to confirm the suitability of the evaluation values obtained and study the relationship between the sensory criteria and the evaluation values. The results confirm that it is possible to fully represent the vibration resistance of an entire floor area based on five impact points and measurement points distributed diagonally on the floor surface, excluding the measurement points within 455 mm of the impact points. Furthermore, calculating the arithmetic mean of the maximum value of the vibration acceleration measured at each measurement point (five points) for each impact point (five points) and each frequency band, and then regarding the vibration acceleration level of each impact point as the evaluation value that is the arithmetic mean or equivalent, demonstrates that the vibration performance could be closely correlated with vibration sensation. Highlights: Calculation of floor impact vibration resistance performance. Evaluation value calculation method for resistance performance of an entire floor. Experiment performed to evaluate vibration sensation. Five impact and measuring points distributed diagonally on floor surface suffice. Vibration performance is closely correlated with vibration sensation.